Preparation of basics for selection of flexible manufacturing structures for rotational parts - Banjac, Dragan; Todić, Velimir; Rodić, Milorad; Gojković, Donka (Journal of Production Engineering, 1994)
The design and utilization of expensive and complex flexible manufacturing systems require a detailed analysis to select the optimum solution concerning accuracy, reliability, flexibility, productivity, and cost-effectiveness in machining and Multipicture. This paper presents a portion of the investigation results pertaining to the definition of necessary technological fundamentals for selecting optimal variations of flexible manufacturing structures for rotational parts. The paper provides a concise overview of practical applications